2013
DOI: 10.1111/vox.12128
|View full text |Cite
|
Sign up to set email alerts
|

The effect of C1‐inhibitor in a murine model of transfusion‐related acute lung injury

Abstract: In a murine model of TRALI, C1-inhibitor attenuated pulmonary levels of C3a associated with improved lung injury scores, but with persistent high levels of inflammatory cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
1
10
2
Order By: Relevance
“…Prior work has demonstrated that LPS administration usually served as the first hit, which resulted in activated neutrophils that adhered to microvascular endothelial cells in the lung . The anti‐mouse MHC Class I antibody (34–1‐2 s) was considered the second hit, which reacted with mouse MHC Class I, H‐2Kd, and H‐2Dd and eventually developed into TRALI . In this study, the preventive immunotherapy of IL‐2 and IL‐2c in TRALI was observed using the above model, and 2 hours were selected as the endpoint of observation for the occurrence of severe TRALI.…”
Section: Discussionsupporting
confidence: 64%
“…Prior work has demonstrated that LPS administration usually served as the first hit, which resulted in activated neutrophils that adhered to microvascular endothelial cells in the lung . The anti‐mouse MHC Class I antibody (34–1‐2 s) was considered the second hit, which reacted with mouse MHC Class I, H‐2Kd, and H‐2Dd and eventually developed into TRALI . In this study, the preventive immunotherapy of IL‐2 and IL‐2c in TRALI was observed using the above model, and 2 hours were selected as the endpoint of observation for the occurrence of severe TRALI.…”
Section: Discussionsupporting
confidence: 64%
“…However, the mechanism by which breast cancer cells undergo proliferation still remains controversial. Complement is known to play important roles as a first defense against microbes, and also participates in diverse physiological processes and contributes to various immune and inflammatory diseases (4,(33)(34)(35). In addition, there is increasing evidence for the contribution of complement activation to cancer progression (12,16).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are not supported by a retrospective cohort study in which no difference was found between a cohort of patients in an intensive care unit who used aspirin and a matched control group (Tuinman et al , ). Prevention of complement activation by C1‐inhibitor also prevented lung injury in a two hit‐animal model (Muller et al , ). Two in vivo animal models showed no effect of immune modulation by corticosteroids (Tamarozzi et al , ; Muller et al , ).…”
Section: Methodsmentioning
confidence: 98%